2013
DOI: 10.1017/jfm.2013.437
|View full text |Cite
|
Sign up to set email alerts
|

Temporal stability of eccentric Taylor–Couette–Poiseuille flow

Abstract: The combined effects of axial flow and eccentricity on the temporal stability properties of the Taylor-Couette system are investigated using a pseudospectral method. Eccentricity is found to stabilize the Couette flow regardless of axial advection intensity. As the axial Reynolds number Re z is increased for any fixed eccentricity e 0.7, the critical mode switches from deformed toroidal Taylor vortices to helical structures with an increasing number of waves, and with helicity opposed to the innercylinder rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 64 publications
(100 reference statements)
0
18
0
Order By: Relevance
“…This case presents similarity with the eccentric Taylor-Couette instability problem (see [27][28][29] and references therein). Indeed, in those problems, the axial wavelength of the critical perturbations is always of the same order of magnitude of the gap.…”
Section: Results Of the Numerical Simulationmentioning
confidence: 62%
“…This case presents similarity with the eccentric Taylor-Couette instability problem (see [27][28][29] and references therein). Indeed, in those problems, the axial wavelength of the critical perturbations is always of the same order of magnitude of the gap.…”
Section: Results Of the Numerical Simulationmentioning
confidence: 62%
“…Substituting the normal mode form into the Navier-Stokes equations (2.6)-(2.11) linearized about Q leads to a generalized eigenvalue problem in ω and q ′ . Following Leclercq et al (2013), this problem was reduced to a much smaller standard eigenvalue problem by eliminating the pressure, boundary points, and one velocity component (w ′ if m = 0 andṽ ′ otherwise) and then solved using standard LAPACK and ARPACK++ routines. The solver was validated against figure 6 of Avila et al (2008) with perfect agreement between our computed values of critical Re and values digitized from the plot for Γ = 3, 4, 6 and the various m shown.…”
Section: Linear Stabilitymentioning
confidence: 99%
“…In this modified bipolar coordinate system, a FourierChebyshev pseudospectral projection method is implemented, with N φ = 2K φ + 1 Fourier modes, and N ξ Gauss-Lobatto collocation points. For more details on the numerical procedure, the reader is referred to Leclercq et al (2013).…”
Section: Basic Flowmentioning
confidence: 99%
“…On the other hand, convective instabilities correspond to wavepackets propagating only in the downstream direction: in the absence of forcing, the system eventually relaxes to its initial state at any fixed location, after perturbations have been 'blown away' from the source. The most temporally amplified perturbations are given by a classical temporal stability analysis, and such a study was recently carried out for this flow (Leclercq, Pier & Scott 2013). It was shown that the physics is essentially similar to the axisymmetric case (Takeuchi & Jankowski 1981;Ng & Turner 1982), with propagating toroidal vortices replaced by helical structures of increasing azimuthal complexity as Re z is increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation